Silicon carbide sensors in radiotherapy dosimetry: progress, challenges, and perspectives - Petringa, G.; Guarrera, M.; Kurmanova, A.; Tudisco, S.; Verona , C.; Cirrone, G. A. P. (Frontiers in Sensors, 2025)
Accurate dosimetry is crucial in radiotherapy and particle therapy to ensure that prescribed doses are delivered to tumors while minimizing damage to healthy tissue. Advanced dosimetry systems are needed to meet the challenges of modern techniques (small fields, high dose gradients, ultra-high dose rates). Silicon carbide (SiC), a wide bandgap semiconductor, has emerged as a promising material for next-generation radiation detectors. This review highlights the role of SiC in dosimetry for photon, electron, proton, and carbon ion beams, including the new FLASH ultra-high dose rate radiotherapy. We summarize SiC’s advantageous physical properties and survey its use in various detector architectures. In conclusion, SiC shows excellent linearity, radiation tolerance, and the potential to complement or outperform conventional dosimeters. Ongoing developments and multidisciplinary research are expected to address remaining challenges and pave the way for SiC’s integration into clinical dosimetry and future high-performance applications.